Effect of Maxillary Lateral Incisor Inclination on Attractiveness Perception of Smile Esthetics among Orthodontists and Laypersons in Close Up and Full Face View - Moghimi, Fatemeh; Salehi Vaziri, Abbas; Ahmadvand, Atefe (Galen Medical Journal, 2024)
Background: Maxillary lateral incisors are crucial in contributing to a pleasing smile. As earlier research has not examined how the labiopalatal inclination of maxillary lateral incisors influences smile appeal, this study sought to investigate this factor from the viewpoints of both laypeople and orthodontists; it also evaluated whether a close-up or full-face view of the smile and the model’s gender influence the attractiveness of the smile. Materials and Methods: Three-dimensional dental models and images of a male and female volunteer were created and subsequently modified to display seven labiopalatal incilination values (-15°, -10°, -5°, 0°, +5°, +10°, and +15°). These were assessed by both orthodontists and laypeople from two perspectives (close-up and full-face) through an online survey. Results: The analysis revealed no significant differences between the full-face and close-up perspectives. However, the male participant with +15° and +10° inclinations demonstrated a noticeably higher level of attractiveness in the full-face view. Laypeople assessed smiles with inclinations of +10° and +15° as more attractive, whereas orthodontists found 0° to be more appealing. Both groups agreed that the inclination of 0° was the most attractive. Conversely, the least appealing smile was considered to be -15° by laypeople, and +15° by the orthodontists. Conclusion: The palatal inclination of the maxillary lateral incisors was deemed more acceptable than labial torque. Furthermore, orthodontists demonstrated a greater level of rigor in their evaluation of the attractiveness of smiles.